Mastocytoma reminiscent of dermatofibroma. - Milano, A. (European Journal of Pediatric Dermatology, 2022)
A mast cell tumor is defined as one (or more up to a conventional maximum of 5) infiltrated skin lesion consisting of mast cells; series that include adults speak of a frequency of 4% (3) among cases of mastocytosis, while in childhood series its frequency reaches 46% (2). Mastocytoma is often present at birth or begins in the first months with an erythematous patch that becomes brown and infiltrated and undergoes episodes of local and generalized histamine release more frequently than maculo-papular mastocytosis; these episodes become less severe after the first two years. (...).